If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7 + c) = 3(c + -4) (7 * 4 + c * 4) = 3(c + -4) (28 + 4c) = 3(c + -4) Reorder the terms: 28 + 4c = 3(-4 + c) 28 + 4c = (-4 * 3 + c * 3) 28 + 4c = (-12 + 3c) Solving 28 + 4c = -12 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 28 + 4c + -3c = -12 + 3c + -3c Combine like terms: 4c + -3c = 1c 28 + 1c = -12 + 3c + -3c Combine like terms: 3c + -3c = 0 28 + 1c = -12 + 0 28 + 1c = -12 Add '-28' to each side of the equation. 28 + -28 + 1c = -12 + -28 Combine like terms: 28 + -28 = 0 0 + 1c = -12 + -28 1c = -12 + -28 Combine like terms: -12 + -28 = -40 1c = -40 Divide each side by '1'. c = -40 Simplifying c = -40
| (2x+3)-19=x | | (8-v)(2v-1)=0 | | 13y+3x=635 | | 9x^2+4y^2-36=0 | | 5b-30=3+8b+72 | | 20p^2-9p-20=0 | | x^4-x^3-42x^2=0 | | 3x+4=44 | | -9n+5(2+6n)=-7n-18 | | 3x+13y=635 | | 56(3x+7)=180 | | (9x-5)(-6x-4)= | | 5=-2 | | 5m-(m+6)=0 | | -2(-4)+(-18)= | | 18x=28x | | 1x=13 | | 4x-2=x-5 | | 6+p=3p-6 | | 11x^2-29=0 | | 2x+3y+3z=250 | | 1+2a+2=3a+12 | | (3+4N)*12N= | | 2y-27=6y+9 | | -5y=55 | | y^2+25=10y | | (3+4N)812N= | | 10z-25+5z-5=5z | | -2(d+5)=3(d-2) | | 0.2c+4=-9 | | 7=2(x+5) | | A=q+qtg |